Factors affecting customer loyalty in Malaysia Airlines Berhad - Wong, Zhi Sheng; Chang, Li Kin; Khou, Jing Kai; Yong, Jie Ying; Chua, Le Lin (2020)
This study is aimed to examine the relationships between the customer satisfaction, customer feedback, service quality, corporate image and reputation and the customer loyalty in the Malaysia Airline Berhad. This research’s survey is conducted with the cooperation of the Malaysia Airline Berhad, a total of 384 respondents have responded to the questionnaire and all of them are the customer of the Malaysia Airline Berhad. The researcher have used different methods to test this research model such as the Reliability test, Pearson Correlation Coefficient and Multiple Linear Regression analysis. Our findings showed that most of the variables are significant related to the customer loyalty, such as the customer satisfaction, service quality, corporate image and reputation. However, the customer feedback is poor and not significant related to the customer loyalty. This study provides some external views, different perspectives and better understanding for the Malaysia Airline Berhad to enhance their customer loyalty in the airline industry Malaysia during this critical period.